Influence of agricultural practices on the composition of macroinvertebrate assemblages in the Neuquén River, Patagonia (Argentina) - Betsabé Lares; Laura B. Parra-Morales; Cristina M. Montagna; Josefina Del Brio; Liliana Monza; Pablo Macchi; Hugo Fernández (Ecología Austral, 2022)
Aquatic species in agricultural areas are often exposed to concentrations of pesticides and fertilizers that can affect the entire community. This study aimed to monitor the presence of nutrients and pesticides (organophosphates and carbamates) and evaluate their effects on the composition of macroinvertebrate assemblages at two sites in the Neuquén River, both upstream (UNR) and downstream (DNR) of an area of intensive cultivation of pome fruit trees. Physicochemical parameters in water samples from UNR and DNR were not significantly different, except for nitrate (NO3-). Pesticides analyzed were below detection limits in water and sediment samples. Insects constituted 52.76% of the total individuals in UNR and, among them, Ephemeroptera was the most abundant taxon (n=419). On the other hand, 67.67% of the individuals in DNR were insects, and most of them belonged to the Order Diptera (n=1156). The abundance of Diptera and Ephemeroptera individuals was significantly different between sites. In addition, the temporal variation of richness within each site showed significant differences (P<0.05). There were 15 shared species and a Jaccard’s abundance-based index indicated 37.8% taxonomic similarity. In summary, there were no significant differences in abundance and diversity between UNR and DNR. However, there were differences in taxa richness and composition, with a low percentage of similarity between sites. The above can be observed in the canonical correspondence analysis, which shows a clear relationship between environmental variables and the distribution pattern of macroinvertebrate assemblages.